Pemanfaatan Family Folder Untuk Optimalisasi Kegiatan Home Visit Pasien Hipertensi - Muhammad Ansari Adista; Zahratul Aini; Syahrizal Syahrizal; Sausan Syadza; Fadhilah Jamal (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Home visit is one of the leading health service programs carried out by the puskesmas in an effort to improve public health. During the home visit, various accurate and up-to-date data will be obtained regarding the health condition of patients, family members, utilization of available facilities at home to support the health of family members, relationships between family members and illnesses suffered by each family member. One of the supporting instruments that can be used to optimize home visit activities as a health service effort is the existence of medical records in the form of a family folder. A home visit service activity for a patient with hypertension in the working area of ​​the Jeulingke Health Center, Syiah Kuala District, Banda Aceh City. Home visit activities to preparation of reports are supervised by supervisors from the Family Medicine Section/Department of the Faculty of Medicine, Syiah Kuala University, Banda Aceh. Home visits were carried out twice in one family. The aim is to evaluate treatment and obtain more information about the patient's health condition, next of kin to the patient's and family's living conditions. Home visit activities are complemented by completing the Family Folder instrument which consists of a genogram, family life cycle, family map, family APGAR, family SCREEM and family life line.